Implikasi Hukum Putusan Mahkamah Agung Nomor 697 K /PID/2025 Terhadap Kedudukan Akta Pernyataan Keputusan Rapat Perseroan Terbatas yang Memuat Keterangan Palsu - Syarifah Azahra (Notaire, 2026)
This legal research aims to analyze the legal implications of Supreme Court Decision Number 697 K/PID/2025 on) the legal position of the Deed of Meeting Resolution Statement that contains false statements. This type of research is normative legal research supported by interview data. The research data uses secondary data in the form of literature studies and direct communication through interview data collection. The data was then analyzed using descriptive-analytical methods.The results of the study show that the false statements in the Deed Meeting of Resolution contradict the lawful elements of the objective validity requirements of the agreement, do not meet the material requirements of an authentic deed, and render it invalid as a basis for amending the company's articles of association because it is null and void. The nature of an authentic deed remains formally attached so that legal nullification still requires a court decision.